Reduced Patient Radiation Exposure during Neurodiagnostic and Interventional X-Ray Angiography with a New Imaging Platform - van der Marel, K.; Vedantham, S.; van der Bom, I.M.J.; Howk, M.; Narain, T.; Ty, K.; Karellas, A.; Gounis, M.J.; Puri, A.S.; Wakhloo, A.K. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Advancements in medical device and imaging technology as well as accruing clinical evidence have accelerated the growth of the endovascular treatment of cerebrovascular diseases. However, the augmented role of these procedures raises concerns about the radiation dose to patients and operators. We evaluated patient doses from an x-ray imaging platform with radiation dose–reduction technology, which combined image noise reduction, motion correction, and contrast-dependent temporal averaging with optimized x-ray exposure settings.MATERIALS AND METHODS: In this single-center, retrospective study, cumulative dose-area product inclusive of fluoroscopy, angiography, and 3D acquisitions for all neurovascular procedures performed during a 2-year period on the dose-reduction platform were compared with a reference platform. Key study features were the following: The neurointerventional radiologist could select the targeted dose reduction for each patient with the dose-reduction platform, and the statistical analyses included patient characteristics and the neurointerventional radiologist as covariates. The analyzed outcome measures were cumulative dose (kerma)-area product, fluoroscopy duration, and administered contrast volume.RESULTS: A total of 1238 neurointerventional cases were included, of which 914 and 324 were performed on the reference and dose-reduction platforms, respectively. Over all diagnostic and neurointerventional procedures, the cumulative dose-area product was significantly reduced by 53.2% (mean reduction, 160.3 Gy × cm2; P < .0001), fluoroscopy duration was marginally significantly increased (mean increase, 5.2 minutes; P = .0491), and contrast volume was nonsignificantly increased (mean increase, 15.3 mL; P = .1616) with the dose-reduction platform.CONCLUSIONS: A significant reduction in patient radiation dose is achievable during neurovascular procedures by using dose-reduction technology with a minimal impact on workflow.CBCTconebeam CTCPKAcumulative dose (kerma)-area product3DRA3D rotational angiographyEAKRphantom-entrance air kerma rateIPDRTimaging platform with dose-reduction technologyIPRreference imaging platformK̇a,rair kerma rate at the fluoroscopic reference pointLATlateral plane of the biplane systemPKAdose (kerma)-area productRAKRimage-receptor (detector) entrance air kerma rate